The capacity to implement Lean Management in the healthcare system in Poland - results of a public consultation - Małgorzata Chmielewska; Renata Lotek-Waćkowska; Stanisław Brzozowski; Zbigniew Tytko; Kinga Dziok-Dmowska; Tomasz Hermanowski (Nofer Institute of Occupational Medicine, 2023)
Background Lean healthcare management is an innovative approach to process management in healthcare organizations. Despite that the Lean principles have been increasingly recognized worldwide as a tool to boost organizational performance, improve the quality of care and curb waste, the Lean methodology can be difficult to implement in some countries. This study seeks to identify the facilitators of and barriers to the implementation of Lean in the healthcare system in Poland. Material and Methods A public consultation was held among 318 representatives of stakeholder groups in the healthcare system in Poland. Data was collected using validated self-administered questionnaires. Statistical analysis was performed using the IBM SPSS Statistics 25 software. Results The study revealed that a large share of respondents believed that the awareness of the existing organizational deficiencies in work practices among stakeholders can greatly facilitate the implementation of Lean in the healthcare system in Poland (50.9%, p < 0.05). The main barriers to the deployment of Lean include lack of awareness of the Lean methodology and its benefits (76.1%, p < 0.001); insufficient institutional support (43.7%), and lack of funding for Lean solutions (32.4%). Conclusions Gaps in the medical curricula and education programs for healthcare professionals concerning the latest process management solutions in healthcare should be addressed in order to raise awareness of the benefits of cooperation with and the active involvement of Lean experts in applying "lean" ideas to improve the organizational performance in healthcare. It is also necessary for policy makers to be aware of the benefits of contemporary process management in healthcare and to support its implementation. Med Pr. 2023;74(1):1-8